Riscos psicossociais para a saúde de trabalhadores efetivos e terceirizados em uma instituição público-privada no Estado do Ceará - Silveira, Samara Silva (2018)
This dissertation aimed to evaluate the psychosocial risks in the work environment of a public-private organization in the state of Ceará, Brazil, and to understand how those risks can impact the health/disease process of its associate and outsourced workers. The existing psychosocial phenomena in work relationships were identified by analyzing subjective processes. By doing so, this study contributes to understand how the worker’s health is impacted by the adverse effects of heterogeneous labor links, based on a psychosociological perspective and on the field study of Worker’s Health. In order to do so, the sign research used the following question as starting point: Which psychosocial risks for the worker’s health can be found in the work environment of a public-private institution? This research considered both quantitative and qualitative methods and is characterized as a case study. Three scales from the Inventory of Work and Illness Risks – ITRA, biosociodemographic questionnaire, and semi-structured interviews were used. As for data treatment, this study is supported by the statistical software SPSS and the Sociological Analysis of Speech. The questionnaire was answered by 312 participants and, after that, 10 workers were interviewed (4 associates and 6 outsourced). The most significant results of the questionnaire suggested critical assessment levels for the factors “Organization of Work Assignments” (70,2%; M = 3,11) and serious levels for “Cognitive Burden” (46,8%; M = 3,48); the results were satisfactory for the factors “Professional Fulfillment” (54,5%; M = 3,98); “Freedom of Expression” (59%; M = 4,19), and “Physical Burden” (74,7%; M = 1,87) and “Lack of Recognition” (58,7%; M = 1,84). The statistical results for the T-test indicated significant differences between associates and outsourced workers for the factors “organization of work assignments”, “socioprofessional relationships”, and “physical burden” factor. The integration of the dathe study emphasizes the following aspects as illness boosters and source of wearness: political interference, pressure for results, bureaucracy of procedures, and lack of management training. As for the heal on of health, the following practices are highlighted: physical activities, religion, and the strong affective link established with the organization and with the co-workers. It was made possible to get a better grasp and understanding of the context of these workers based on own perspective. Additionally, the results of this research support the findings of other studies as pointed out by the literature, such as the vulnerabilization and precarization of people who provide outsourced services.